2003
DOI: 10.1161/01.str.0000090348.52943.a2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence, Mortality, and Survival Rate of Cardiovascular Disease in a Japanese Community

Abstract: Background and Purpose-The slowdown of a steeply declining trend in cardiovascular mortality has been reported in Japan, but precise reasons for this trend are uncertain. Methods-We established 3 study cohorts of Hisayama residents aged Ն40 years without a history of stroke or myocardial infarction in 1961 (1618 subjects, first cohort), 1974 (2038 subjects, second cohort), and 1988 (2637 subjects, third cohort). We followed up with each cohort for 12 years, comparing the incidence, mortality, and survival rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
334
5
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(358 citation statements)
references
References 29 publications
14
334
5
2
Order By: Relevance
“…2 With aging of the population, stroke has become an ever more important health burden in Japan, and thus activities aiming at stroke prevention require urgent attention. Elevated blood pressure (BP) has emerged as one of the prominent risk factors for stroke.…”
Section: Introductionmentioning
confidence: 99%
“…2 With aging of the population, stroke has become an ever more important health burden in Japan, and thus activities aiming at stroke prevention require urgent attention. Elevated blood pressure (BP) has emerged as one of the prominent risk factors for stroke.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hypertension is the most common cause of CAD and heart failure in Japan, and cerebrovascular disease is even more prevalent in the Japanese population than in Western societies. 4 The percentage of cerebral bleeding is two or three times greater than in Caucasian people in Europe and in the United States, and cerebral infarction is mostly caused by lacunar type ischaemic stroke owing to hypertensive small vessel disease. 5 The incidence of athero-thrombotic infarction or cardio-embolic infarction is currently increasing in Japan, and the dominant pathogenetic factor for stroke is changing from small arterial disease to large arterial disease in Japanese hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of IHD can be considerably improved by identifying the most important risk factors of the condition and reducing their occurrence. In the Hisayama study, 3 stroke mortality continuously declined and survival significantly improved. In contrast, the only parameter linked to an increased incidence of CHD and CHD mortality was advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many Japanese have easy access to hospitals and frequently undergo medical examinations, yet the prevalence and prognostic indicators of IHD remain unclear in healthy Japanese subjects. The Framingham Heart Study 2 and the Hisayama study 3 have shown the long-term natural prognosis of IHD, but their findings provide only limited help to people in the prime of their lives who wish to know the most important parameters likely to disturb and threaten their present quality of life and portend disadvantages in the future due to IHD. We sought to identify prognostic indicators for IHD in the short term, an issue scarcely evaluated by previous studies.…”
Section: Introductionmentioning
confidence: 99%